2008
DOI: 10.1111/j.1745-7254.2008.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the inhibitory potential of 6 fluoroquinolones on CYP1A2 and CYP2C9 in human liver microsomes

Abstract: Aim: To determine the inhibitory potential of 2 new fluoroquinolones, caderofloxacin and antofloxacin, together with 4 marketed fluoroquinolones, moxifloxacin, gatifloxacin, levofloxacin, and ciprofloxacin, on the activity of cytochrome P450 isoforms 1A2 (CYP1A2) and 2C9 (CYP2C9). Methods: Probe substrates, phenacetin (CYP1A2), and tolbutamide (CYP2C9) were incubated with human liver microsomes and the metabolites were analyzed by liquid chromatography/mass spectrometry using electrospray ionization in positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…However, the results indicate that the acute or chronic administration of caderofloxacin did not change the activity of CYP1A2. This finding agrees with a previous study, which reported that caderofloxacin is a negligible inhibitor of CYP1A2 in human microsomes [41] . In conclusion, the activity of hepatic CYP2E1 increased as a result of the elevated mRNA and protein levels of hepatic CYP2E1 induced by the chronic administration of caderofloxacin.…”
Section: Wwwnaturecom/aps Liu L Et Alsupporting
confidence: 94%
“…However, the results indicate that the acute or chronic administration of caderofloxacin did not change the activity of CYP1A2. This finding agrees with a previous study, which reported that caderofloxacin is a negligible inhibitor of CYP1A2 in human microsomes [41] . In conclusion, the activity of hepatic CYP2E1 increased as a result of the elevated mRNA and protein levels of hepatic CYP2E1 induced by the chronic administration of caderofloxacin.…”
Section: Wwwnaturecom/aps Liu L Et Alsupporting
confidence: 94%
“…Her use of 2 bottles per month is equivalent to 20 mg of dexamethasone per month which is around 0.7mg of dexamethasone per day, which is high for a 6-year-old girl. Moxifloxacin does not inhibit or stimulate the hepatic microsomal P450 system and hence has no effect on steroid metabolism (8). Since drops were used instead of nasal spray, it is likely that a significant amount would be swallowed and absorbed from the gastrointestinal tract, resulting in CS.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed model input parameters were also listed in Table 1. The in vitro IC50 value on the CYP1A2 measured by Zhang et al was also used for this DDI simulation [28]. Population mean age, dose, dose interval and the duration of administration of ciprofloxacin and caffeine were determined according to the regimen of the clinical DDI studies.…”
Section: Methodsmentioning
confidence: 99%